2010
DOI: 10.1111/j.1523-536x.2010.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Guided Imagery on Blood Pressure in Pregnant Women with Hypertension: A Pilot Randomized Controlled Trial

Abstract: Further rigorous study is warranted to determine effects of guided imagery on maternal blood pressure and perinatal health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
0
13
1
6
Order By: Relevance
“…17,19,57 The significant decrease in systolic blood pressure found in this study suggests a beneficial effect of GI on the SAM system. 56 The findings also support the feasibility of conducting a randomized clinical trial of a holistic GI intervention. 28,69 Other studies 20,56 have not documented similar results, and this inconsistency may be explained by methodological differences.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…17,19,57 The significant decrease in systolic blood pressure found in this study suggests a beneficial effect of GI on the SAM system. 56 The findings also support the feasibility of conducting a randomized clinical trial of a holistic GI intervention. 28,69 Other studies 20,56 have not documented similar results, and this inconsistency may be explained by methodological differences.…”
Section: Discussionmentioning
confidence: 55%
“…56 While there was a trend toward better responses for blood pressure in the GI group than in the quiet rest group, no statistical differences were found. Of the limited research, one study recruited hypertensive pregnant women (n = 69) from either an outpatient or a hospital setting and randomized them to an intervention that required either listening for 15 minutes to GI being played with background music twice a day for 4 weeks or taking 15 minutes of quiet rest for the same duration.…”
Section: Guided Imagerymentioning
confidence: 80%
See 1 more Smart Citation
“…Likewise, Moffatt et al. (21) showed there is no evidence of GI effect on blood pressure and anxiety in pregnant women; however, nearly 90% of the GI group indicated that they would use it again. Moreover, Chen and Francis’s (22) results indicated consistent and clinically significant trends of improvement on pain, mental health, all domains of quality of life and sleep for the GI group only.…”
Section: Introductionmentioning
confidence: 98%
“…The paper by Wight Moffatt et al (1) provides a novel approach to evaluate the extremely common problem of hypertension in pregnancy. This pilot study randomized 69 hypertensive pregnant women to periods of either guided imagery or quiet rest.…”
mentioning
confidence: 99%